Bartholin's gland abscess in a prepubertal female: A case report. (December 2017) - Radhakrishna, Veerabhadra; Goel, Rachit; Parashar, Gaurav; Santhanakrishnan, Ramesh
Abstract: Bartholin's gland abscess is one of the common inflictions of vulva seen in females of reproductive age group with a recurrence rate of up to 38%. Although it's encountered by many Paediatric Surgeons, it's very rarely reported in prepubertal age. Till date, only six cases have been reported to the best of our knowledge. A seven-year-old female child presented with a recurrent labial abscess. She was found to have Bartholin's gland abscess and was treated with partial excision of cyst wall along with the overlying mucosa and drainage. There has been no recurrence for the past six months at follow-up. Bartholin's gland abscess, although rare in children, should be considered as one of the differential diagnosis of a labial swelling. Adequate drainage is essential to prevent recurrence. Highlights: Bartholin's gland abscess, although rare in children, should be considered as one of the differential diagnosis of a labial swelling. It has a recurrence rate of up to 38%. Its notorious nature of recurrence can be prevented by partial excision of the cyst wall, incision and curettage, marsupialization, or placement of a word catheter or a rubber drain.